Near Eastern Landscapes and Declassified U2 Aerial Imagery. Issue 2 (12th March 2019) - Hammer, Emily; Ur, Jason
Abstract: Recently declassified photographs taken by U2 spy planes in the 1950s and 1960s provide an important new source of historical aerial imagery useful for Eurasian archaeology. Like other sources of historical imagery, U2 photos provide a window into the past, before modern agriculture and development destroyed many archaeological sites. U2 imagery is older and in many cases higher resolution than CORONA spy satellite imagery, the other major source of historical imagery for Eurasia, and thus can expand the range of archaeological sites and features that can be studied from an aerial perspective. However, there are significant barriers to finding and retrieving U2 imagery of particular locales, and archaeologists have thus not yet widely used it. In this article, we aim to reduce these barriers by describing the U2 photo dataset and how to access it. We also provide the first spatial index of U2 photos for the Middle East. A brief discussion of archaeological case studies drawn from U2 imagery illustrates its merits and limitations. These case studies include investigations of prehistoric mass-kill hunting traps in eastern Jordan, irrigation systems of the first millennium BC Neo-Assyrian Empire in northern Iraq, and twentieth-century marsh communities in southern Iraq. Abstract : Las fotografías tomadas por aviones espía U-2 durante los años 50 y 60, recientemente desclasificadas, son una nueva fuente de imágenes aéreas muy útil para la arqueología euroasiática. Tal como otras fuentes de imágenes históricas, las fotografías de los U-2 son una ventana hacia un pasado antes de la destrucción de muchos sitios arqueológicos a manos de la agricultura y el desarrollo modernos. Las imágenes de los U-2 preceden aquellas tomadas por los satélites espía CORONA, la otra fuente principal de imágenes históricas de Eurasia, y en muchos casos son de más alta resolución. Por lo mismo, expanden el rango de sitios y rasgos arqueológicos que se pueden estudiar desde una perspectiva aérea. Sin embargo, existen obstáculos significativos para conseguir y acceder a imágenes de localidades particulares, y por lo tanto los arqueólogos todavía no acostumbran a valerse de ellas. En este artículo tenemos como meta disminuir estos obstáculos a través de una descripción del conjunto de imágenes de los U-2 y de un método para acceder a ellas. También proveemos el primer índice espacial de fotografías de los U-2 del Medio Oriente. Una breve discusión de casos prácticos usando estas imágenes demuestra sus ventajas y limitaciones. Estos casos incluyen investigaciones de trampas de caza prehistóricas en el este de Jordania, sistemas de irrigación del imperio Neo-asirio del primer milenio a.C. en el norte de Irak y de comunidades del siglo XX que habitaban en los humedales del sur de Irak.